Focus group methodology : principles and practice - Liamputtong, Pranee, 1955- (London : SAGE, 2016)
An introductory text which leads readers through the entire process of designing a focus group study, from conducting interviews and analyzing data to presenting the findings. The author presents clear, practical advice in simple terms which will be appropriate for undergraduate and postgraduate students who are undertaking research.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 13, 2016).
Keywords: elektronické knihy; electronic books; Focus groups